Induced sputum to detect lung pathogens in young children with cystic fibrosis. Issue 2 (30th November 2016) - D'Sylva, Pamela; Caudri, Daan; Shaw, Nicole; Turkovic, Lidija; Douglas, Tonia; Bew, Jane; Keil, Anthony D.; Stick, Stephen; Schultz, André
Summary: Introduction: Induced sputum sampling holds promise as a method for obtaining samples representative of the lower airways in young children. Collection of induced sputum samples in young children differs from older children and adults' as pharyngeal suctioning is often required. Our aim was to determine the sensitivity and specificity of induced sputum with and without airway clearance techniques to detect lower airway pathogens in children less than age 7 with cystic fibrosis. Methods: Microbiological culture results were compared between 61 paired induced sputum and bronchoalveolar lavage fluid samples from young children with cystic fibrosis. The first cohort received no airway clearance and the second cohort received airway clearance. Induced sputum was sampled within 7 days of bronchoscopy. Results: Median age (range) of participants was 3.3 years (0.9–6.7). Sensitivity and specificity (95%CI) of induced sputum was 36.8% (16.3, 61.6), and 69% (52.9, 82.4), respectively (N = 61). In subgroup analysis, induced sputum with (N = 31) and without airway clearance (N = 30) demonstrated sensitivity of 50% (15.7, 84.3) and 27.3% (6.0, 61.0), respectively, and specificity of 60.9% (38.5, 80.3), and 78.9% (54.4, 93.9), respectively. Conclusion: Induced sputum is not highly sensitive or specific as routine surveillance for detection of lower airway pathogens in young children with cystic fibrosis.Pediatr Pulmonol. 2017;52:182–189. © 2016 Wiley Periodicals, Inc.